Global Induced Stress Field From Large Earthquakes Since 1900 and Chained Earthquake Occurrence - Junhyung Lee; Tae‐Kyung Hong (Geochemistry, Geophysics, Geosystems, 2021)
Abstract Megathrust earthquake occurrence is dependent on the physical properties and stress environments of convergent plate boundaries. Local and regional earthquakes may modulate the stress environment fractionally that affects the nucleation of next earthquakes. This study investigates the influence of precedent earthquakes on the induction of forthcoming earthquakes around the circum‐Pacific plate boundaries. We assess the global stress perturbation induced by 1,636 earthquakes combining 1,457 earthquakes with moment magnitudes greater than or equal to MW7.0 and 179 earthquakes with moment magnitudes MW6.4–6.9 in 1900–2020. We stack the induced Coulomb stress changes for optimally oriented reverse faults. The circum‐Pacific region is divided by eight subregions. The cumulative Coulomb stress changes reach up to the order of tens to hundreds of bar at the convergent plate boundaries. Descendant large earthquakes dominantly occurred in the regions with large lateral gradients of cumulative Coulomb stress changes induced by precedent earthquakes. The cumulative Coulomb stress changes for 120 years are comparable among subduction zones. The seismicity in subduction zones may depend on the strength of the stress field as well as the lateral gradient in the stress field. The instability and inhomogeneity in stress fields may play a major role in the nucleation of megathrust earthquakes.